Implications of the management of a dry pasture cultivated in response to fertilization - Terroba, Nicaela (2024)
The nutrient use in forages livestock system production high Andean is little used. This study evaluated the response of fertilization on the association of cultivated grasses in dry of Dactilys (Dactylis glomerata var. Potomac) and red clover (Trifolium pratense var quiñequeli). The study area was located at 4350 m of altitude in to the Puna ecoregion in Ayaracra sector, Pasco region of Peru. The experimental design was randomized complete block with factorial 2x3x2; with two levels of nitrogen (0 to 50 kg/ha), three levels of phosphorus (0, 80 to 160 kg/ha) and two levels of potassium (0 to 30 kg/ha). Was evaluated were floristic composition, growth rate and pasture production. The results indicate that fertilization nitrogen (50 kg/ha) and phosphorus (80 kg/ha) showed effect a significant the growth rate and forage production. There was not an effect potassium fertilization on the variables evaluated. The analysis of the interactions indicates that the combination of N 50, P 80 and K 0 showed gave better results in forage production than the other treatments.